Optimising Students’ Self-Confidence Through Group Guidance Using the Self-Talk Technique - Izwan Ardhian Saragih; Nurussakinah Daulay (Journal of General Education and Humanities, 2026)
This study aimed to examine the effectiveness of group guidance services using the self-talk technique in optimising the self-confidence of eighth-grade students at SMP Swasta Al Washliyah 26 Medan. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research sample consisted of 14 students with low levels of self-confidence, who were divided into an experimental group and a control group. The research instrument was a self-confidence scale consisting of 36 statement items that had met the validity and reliability requirements. Data analysis was conducted using an independent samples t-test with the assistance of SPSS version 26. The results indicated that all students in the experimental group experienced an improvement in self-confidence from the low category to the high category after receiving group guidance services with the self-talk technique. Statistical testing showed a significance value of 0.004 (< 0.05), indicating a significant difference between the experimental group and the control group. The mean posttest score of the experimental group (116.71) was higher than that of the control group (108.86).